Biofuels from algae: Physiological characterization of candidate diatom species - Pilný, Jan (Jihočeská univerzita, 2010)
The aim of this study was to isolate and extensively test promising candidate diatom species for biodiesel cultivation. Diatom strains were isolated from natural habitats in the state of Ohio (USA). These strains were tested to find optimal growing conditions and media (concentration of Nitrogen, Phosphorus, Silica, source of Nitrogen, temperature etc.).
Biofuels from algae: Physiological characterization of candidate diatom species
Keywords: rozsivky; kultivace; růst; diatoms; cultivation; growth